The work of a student to solve the equation 4(2x − 4) = 8 + 2x + 8 is shown below:

Step 1: 4(2x − 4) = 8 + 2x + 8
Step 2: 6x − 8 = 16 + 2x
Step 3: 6x − 2x = 16 + 8
Step 4: 4x = 24
Step 5: x = 6

In which step did the student first make an error and what is the correct step? Step 2; 8x − 4 = 2(6 + x + 6)
Step 2; 8x − 16 = 16 + 2x
Step 3; 6x − 2x = 16 − 8
Step 3; 6x + 2x = 16 + 8

Respuesta :

Step-by-step explanation:

Here, The work of a student to solve the equation :

[tex]4(2x-4)=8+2x+8[/tex]

The steps for calculating the value of x are :

Step 1: 4(2x − 4) = 8 + 2x + 8  

Step 2: 6x − 8 = 16 + 2x  

Step 3: 6x − 2x = 16 + 8  

Step 4: 4x = 24  

Step 5: x = 6

Step 2 is incorrect, as the student instead of multiplying, adds the number as :

4(2x − 4) = 8 + 2x + 8  

Here, the correct step is :

8x − 16 = 16 + 2x

6 x = 32

x = 5.33

So, the error is in STEP 2 and the correct option is (b).

Answer:

It's B, Step 2; 8x − 16 = 16 + 2x

Step-by-step explanation:

yw and gl

ACCESS MORE